Social Service (PKM) at Binakheir Kindergarten in Sentul, Bogor (E-Commerce Training for Product Marketing): PKM Pada Pra TK/TK Binakheir Sentul-Bogor (Pelatihan E-Commerce untuk Pemasaran Produk) - Suryadi, Ahmad; Rosa, Novrita Mulya; Hidayatullah, Reko Syarif (Yayasan Ahmar Cendekia Indonesia, 2020)
Information technology not only affects an information system, but also affects everyday life. These influences include lifestyles that begin to change along with the growth of information technology products. One of the information technologies applied in the marketing world is the application of popular e-commerce based marketing media. The problem found at Binakheir Kindergarten was that the income of teachers and staff was still insufficient to meet their daily needs. Referring to this matter, the enthusiasm in carrying out tasks was reduced. The next problem encountered was that teachers do not understand and do not have any skill in creating and managing an online store. This community service activity was carried out with the aim of increasing knowledge and improving teachers’ skills in entrepreneurship and utilizing e-commerce as a medium for marketing the products they sell. The preparation stages applied in this activity consisted of partner surveys, licensing and material preparation. While the implementation stage of this activity included the socialization method of program introduction presentations, discussions and the practice of creating and managing an online store. The evaluation stage of this activity aimed to determine the ability of partners before and after the training. The results of this conducted activity indicated that there was an interest in entrepreneurship that arises from partners and an increase in partners’ knowledge and skills in creating and managing online stores. Abstrak Teknologi Informasi tidak hanya mempengaruhi sebuah system informasi, namun memiliki pengaruh dalam kehidupan sehari-hari, gaya hidup mulai berubah seiring dengan pertumbuhan produk-produk teknologi informasi yang semakon berkembang. Impementasi teknologi informasi dalam dunia pemasaran, salahsatunya melalui penerapan media pemasaran berbasis e-commerce popular. Permasalahan yang ditemukan di Pra TK / TK Binakheir yaitu penghasilan para guru dan staf yang belum cukup untuk memenuhi kebutuhan keseharian mereka. Hal ini menyebabkan berkurangnya semangat dalam menjalankan tugas. Permasalahan berikutnya adalah guru belum memahami dan memiliki ketrampilan dalam pembuatan dan pengoperasionalan toko online. Tujuan kegiatan pengabdian masyarakat ini adalah untuk menambah pengetahuan dan meningkatkan ketrampilan guru dalam berwirausaha dan memanfaatkan e-commerce sebagai media pemasaran produk yang mereka jual. Tahap persiapan terdiri dari survey ke mitra, perijinan dan penyiapan meteri Tahap pelaksanaan menggunakan metode sosialisasi presentasi pengenalan program, diskusi dan praktik pembuatan dan pengoperasionalan toko online. Tahap Evaluasi kegiatan bertujuan untuk mengetahui kemampuan mitra sebelum dan sesudah pelatihan. Hasil dari kegiatan adalah timbulnya minat berwirausaha dari mitra dan erjadinya peningkatan pengetahuan dan keterampilan mitra membuat dan mengelola toko online.